Recent advances and perspectives in photo-induced enhanced Raman spectroscopy. Issue 19 (7th May 2021) - Zhao, Jingtian; Wang, Ziyun; Lan, Jinshen; Khan, Imran; Ye, Xiaofang; Wan, Jing; Fei, Yuchen; Huang, Shengli; Li, Shuping; Kang, Junyong
Abstract : Light irradiation induces charge separation and expels electrons to the states of oxygen vacancies or the conduction band, which increases the charge transfer and electromagnetic field of the substrate and magnifies the Raman signal of the analytes. Abstract : Phototreatment is at the leading edge of a research hot topic as a driving force for structural transformation, spectral and electromagnetism improvements, and the functional performance of nanomaterials. Light irradiation can excite surface plasmons in noble metal nanoparticles, create electron–hole pairs, and produce charge transfer in semiconductor substrates, which have led to it being widely used in surface-enhanced Raman spectroscopy (SERS) for life sciences, environmental protection, and biological analysis. Photo-induced enhanced Raman spectroscopy (PIERS) is a new technology developed on the basis of traditional SERS and has proven to be an efficient way to resolve several critical challenges thanks to its incomparable superiority for incontiguous operation, efficient charge separation and enrichment, and a large signal enhancement for a wide range of biomolecules at the trace level. This makes PIERS a powerful technique with very appealing and promising applications in various branches of analytical science. In this review, the enhancement mechanisms of PIERS are analyzed in comparison with SERS. Afterward, the parameters influencing the enhancement of PIERS, including the substrate, light irradiation, and relaxation are discussed in detail. Finally, some perspectives on further developments of PIERS are exemplified. The PIERS technique will continue to evolve and grow with new developments and its successful application in bioanalysis and life sciences.